2018
DOI: 10.1136/archdischild-2018-315951
|View full text |Cite
|
Sign up to set email alerts
|

Home use of breast milk fortifier to promote postdischarge growth and breast feeding in preterm infants: a quality improvement project

Abstract: To improve the postdischarge growth of exclusively breastfed preterm infants, born weighing ≤1.8 kg, by using breast milk fortifier (BMF) supplements postdischarge until 48 weeks’ gestational age. A quality improvement (QI) project involving plan–do–study–act (PDSA) cycles. A tertiary surgical neonatal unit. Preterm infants weighing ≤1.8 kg at birth. We completed four PDSA cycles to develop and improve an electronic patient information sheet to promote the use BMF beyond discharge. Safety, feasibility and atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…In accordance with this there have been recommendations that fortifier is continued in preterm breast fed babies either to term or around 52 weeks post conceptional according to their growth trajectory (103, 113). Although the practicality of putting this into practice has been questioned by some reviewers because of the availability of HMF in different countries and the perceived, but not proven, problems with practicability (106), evidence is accruing that it is possible using many different methods (114).…”
Section: Post Discharge Fortificationmentioning
confidence: 99%
“…In accordance with this there have been recommendations that fortifier is continued in preterm breast fed babies either to term or around 52 weeks post conceptional according to their growth trajectory (103, 113). Although the practicality of putting this into practice has been questioned by some reviewers because of the availability of HMF in different countries and the perceived, but not proven, problems with practicability (106), evidence is accruing that it is possible using many different methods (114).…”
Section: Post Discharge Fortificationmentioning
confidence: 99%
“…A longer response window or different method of distributing the survey may have elicited a higher response rate. A previous survey of the same specialist group had a higher response rate (66%) but a lower number of respondents ( n = 27) ( 13 ) . Previous studies on the use of BMF in other healthcare professionals have elicited a wide variation in response rates, from an exceptional online response rate of 98% ( 14 ) compared to 26% in a postal survey ( 15 ) .…”
Section: Discussionmentioning
confidence: 95%
“…Neither trial found a statistically significant difference in the overall duration of breastmilk feeding; however, one of the studies reported that statistically significantly fewer infants in the BMF group remained exclusively breastfed (no formula) at 4 months ( 33 ) . Subsequently, a UK‐based quality improvement study has demonstrated that the growth trajectory of exclusively breastfed preterm infants discharged home on BMF was improved up to 1 year of age, with parents and healthcare professionals finding the use of home BMF supplement to be acceptable, feasible and safe ( 13 ) . Overall, there is an absence of evidence on the effect of using BMF post‐discharge on long‐term growth and developmental outcomes beyond 1 year corrected age and it is recommended that any future interventions are developed in conjunction with families and consider the potential for interference on breastfeeding ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seguindo a mesma linha raciocínio, de maneira geral, esse fator também é observado nos ganhos de peso e comprimento em bebês que se encontram em leite materno exclusivo, Toftlund et al (2018) apresenta em sua pesquisa dados de que crianças que amamentaram, apresentaram maior crescimento e peso entre a faixa etária de 3 a 6 anos. Da mesma forma que, em prematuros também observa-se esses ganhos, principalmente pela busca de compensar o quão imaturo o fisiológico se encontra (Halleux et al, 2019& Marino et al, 2019.…”
Section: Discussionunclassified